2021
DOI: 10.1186/s12905-021-01538-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mammographic breast density among women in Karachi Pakistan

Abstract: Background There are no studies done to evaluate the distribution of mammographic breast density and factors associated with it among Pakistani women. Methods Participants included 477 women, who had received either diagnostic or screening mammography at two hospitals in Karachi Pakistan. Mammographic breast density was assessed using the Breast Imaging Reporting and Data System. In person interviews were conducted using a detailed questionnaire, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Risk factors identified include a family history of breast cancer, early menarche, late menopause, positive family history, and obesity ( 25 ). Viral infections, genetic mutations, lack of knowledge about breast cancer symptoms and risk factors, and low vitamin D levels are also associated with an increased risk of breast cancer ( 26 32 ). The prevalence of BRCA1/2 mutations is higher in Indian breast and/or ovarian cancer patients, and delays in the diagnosis and treatment of breast cancer are associated with poor referral systems ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors identified include a family history of breast cancer, early menarche, late menopause, positive family history, and obesity ( 25 ). Viral infections, genetic mutations, lack of knowledge about breast cancer symptoms and risk factors, and low vitamin D levels are also associated with an increased risk of breast cancer ( 26 32 ). The prevalence of BRCA1/2 mutations is higher in Indian breast and/or ovarian cancer patients, and delays in the diagnosis and treatment of breast cancer are associated with poor referral systems ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Age, weight, and breast density are highly correlated with the incidence of BC ( 80 ). According to a study in Pakistani Asian women, younger females are more affected by BC and its prevalence increased from 70% to 130% among females aged 30 to 34 years and among the age group 50-64 years, the percentage prevalence increased from 23.1% to 60.7% ( 26 ) ( Table 1 ). Particularly, the incidence of metastatic BC and high-grade BC in young females has escalated in the past few years.…”
Section: Asiamentioning
confidence: 99%
“…The study revealed that most of the participants were not aware that BD decreases with age, increases with childbearing, and also has no relation with breast size. Studies done in different regions observed a significant association of BD with age in which BD decreases as women age especially those in the menopausal stage [17][18][19]. In relation to childbearing, the study of Yaghjyan et al found a positive relation between childbearing in terms of breastfeeding and BD of premenopausal women [20].…”
Section: Discussionmentioning
confidence: 99%
“…Increased breast density is related to hormone replacement therapy (HRT) use after menopause, high alcohol consumption, a family history of breast cancer within first-degree relatives, a history of benign breast disease, older age at first birth, nulliparity, higher height and older age at menopause (Kerlikowske et al ., 2010; Dorgan et al ., 2012; Alexeeff et al ., 2019; Azam et al ., 2019; Shamsi et al ., 2021; Han et al ., 2022). In contrast, increased age, higher BMI, ever-smoked, younger age at menarche and oral contraceptive use showed an inverse association with breast density (Checka et al ., 2012; Azam et al ., 2019; Moore et al ., 2020; Shamsi et al ., 2021), suggesting an opposite association with breast cancer. However, most studies on the determining factors for breast density were conducted in Western populations, and studies in Asian populations were limited to a small number of study participants (Sung et al ., 2018; Hanis et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%